International Humanitarian Aid - Alvarez-Gutierrez, Sergio Alex (2023)
International relief in the health sector represents support to the affected countries, especially in the face of theoccurrence of natural phenomena that generate multi-hazard events, such as the El Niño Phenomenon. When the responsecapacity of the operators up to the regional government is exceeded, level IV and V of national emergency can be declaredactivating response mechanisms in the central level instances and concomitantly in international cooperation through theNational Humanitarian Network. International relief is deployed based on criteria that are taken into account by globalresponse mechanisms, such as responding to real needs, establishing coordinated efforts, availability in the shortest time, anavailable logistics chain, and meeting immediate needs; criteria that seek to reduce the deaths and suffering of people in theaffected area. Likewise, making available to the countries the multi-threat response framework, emergency medical teams andthe resources that are required by the country, makes it possible to diversify operations, depending on the needs and timing ofthe aid required by the affected country, according to to global availability. It should be remembered that the interventionscarried out with the support of cooperation seek to complement the efforts made by the government and its health sector, so it is suggestive to generate an exit or transfer strategy to move from response to recovery and finally development.